2003
DOI: 10.1007/s00535-003-1119-6
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of tumor suppressor gene p16 in pancreatic carcinoma: immunohistochemical and genetic findings compared with clinicopathological parameters

Abstract: These findings suggest that p16 alterations may participate in the aggressiveness of pancreatic carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
2
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 42 publications
5
31
2
2
Order By: Relevance
“…A study evaluating the prognostic value of p16 mutation in patients with PC found that the tumour was significantly larger and the survival period significantly shorter for patients with PC with p16 mutation or hypermethylation than for those with pancreatic carcinoma with an intact p16 gene, suggesting that p16 alterations may participate in the aggressiveness of pancreatic carcinoma [48].…”
Section: K-rasmentioning
confidence: 99%
“…A study evaluating the prognostic value of p16 mutation in patients with PC found that the tumour was significantly larger and the survival period significantly shorter for patients with PC with p16 mutation or hypermethylation than for those with pancreatic carcinoma with an intact p16 gene, suggesting that p16 alterations may participate in the aggressiveness of pancreatic carcinoma [48].…”
Section: K-rasmentioning
confidence: 99%
“…It is difficult to predict which patient is at risk of early relapse following surgery, or which patient with advanced stage disease will show good long-term survival. K-ras point mutations and inactivation of p53, p16, and SMAD4 are often associated with malignant characteristics in pancreatic cancers, but mutations of K-ras and p53 are not significantly associated with the prognosis of patients with pancreatic cancer (21,23,24). In the prognosis of patients with pancreatic cancer, there seems to be a significant correlation between microvessel density and the expression of vascular endothelial growth factor (VEGF) and PD-ECGF in the tumor, as well as with E-cadherin, p27, PEDF, and SMAD4 expression (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…This abstract has only four non-standard references to mutation: "CDKN2A alterations" (one instance) and "(epi)genetic modifications" (three instances). Similarly, articles PMID: 12898359 (Ohtsubo, et al, 2003) and PMID: 12721243 (Schneider-Stock, et al, 2003) both mention "mutation(s)" and either "homozygous deletion" or "loss of heterozygosity" sporadically, but each usually instead refers to "abnormalities", and the focus of the articles are on methylation status and immunohistochemical analysis of tumors. PMID:11159196 (Schraml, et al, 2001), specifically mentions "mutation analysis" and "24-bp deletion" as the only two direct instances of mutation mentions, while most of the abstract describes results of a chromosomal deletion analysis.…”
Section: Resultsmentioning
confidence: 99%